Caminhos e desafios da formação de educadores de jovens e adultos - Rosa Cristina Porcaro (2011)
The work has as central theme of the training of educators and young adults. The Youth and Adults (EJA) has expanded institutionally in the country, deserving of greater attention from government agencies. However, although expanding, is still being developed by teachers without special training. This situation causes weakness in the daily practice of these professionals, who develop the work without a consistent knowledge base in the area of adult education. The study proposal was then to investigate the training of educators and young adults, identifying the challenges that stand in building their professional teaching in such educational setting. Specifically, we sought to: investigate the configuration of the teaching profession in the educational context of Adult and Youth analyze the inclusion of professional educator EJA, identify challenges and opportunities that permeate the field and training of educators; analyze the look of these educators relation to their profession and the impact of experiential references them in the process of its construction work. The fundamental issues were: who is the educator who works with adult education? Training that he brings to the development of your work? How is their employment in adult education? What difficulties and challenges lies in developing the work? What paths searching for the confrontation of the challenges? Have to look over his career training? For the theoretical study, we developed a dialogue with some authors, who provided important contributions are essential to the analysis of the issue, as Paulo Freire, Júlio Diniz-Pereira, Maria da Conceição Fonseca, Donald Schon, Marta Kohl de Oliveira, Maria Margarida Machado, Francisco Carlos Franco, Kenneth Zeichner, Claude Dubar, George Gaskell, and others. To meet the objectives proposed, were chosen the following ethodology: a step of questionnaires to twenty-five youth and adult educators, one from each state, and a stage ofindividual interviews, done with eight educators selected among those ho answered the questionnaire, seeking insight into the history of insertion and training of these educators. Some results obtained from the research were: educators have investigated diverse background and demonstrate some degree, but without specific training in adult education. In the absence of specific resources for the job, build a didactic approach, considering the specificity of the learners. Within a professional environment of lack of resources, support and alternatives, appear committed to the cause, interested in doing a good job individually and seek their education. Key features of the commitment and resilience, surrounded by all sorts of difficulties in their teaching, dealing with these difficulties in order to overcome them and become better prepared professionally from this confrontation. Its formation takes place, therefore, in daily life, coping with the difficulties that stand in their practice and seeking alternatives to overcome these difficulties. The construction of their professional teaching experience occurs as the specific reality of AYE and, from there, create alternative actions, using the resources available to them. Identifies among them the value of listening and accommodating their students. Finally, these teachers not only create alternative work or even learn from their own experiences, but mainly fall into a tradition and try to redeem the bonds with popular education, such as tax, and recreators followers of a tradition